2020
DOI: 10.1111/pin.13011
|View full text |Cite
|
Sign up to set email alerts
|

The circRNA circ_0000291 acts as a sponge of microRNA 326 to regulate E26 transformation‐specific sequence‐1 expression and promote breast cancer progression

Abstract: Accumulating studies authenticate that circular RNAs (circRNAs) are involved in the progression of cancers. However, their role in breast cancer (BC) remains largely unknown. In this study, real‐time polymerase chain reaction was employed to detect the circ_0000291 and miR‐326 expressions in BC tissues and cells. The correlation between the expression level of circ_0000291 and clinicopathological parameters of BC patients was analyzed. Western blot was used to detect the expression of E26 transformation‐specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…CircRNAs are a sort of circular ncRNAs that widely exist in eukaryotes, and their structures are stable and highly conserved (H. D. Zhang, Jiang, et al, 2018). Researches have shown that circRNA is nearly connective with the pathogenesis of tumors and can effectively regulate tumor cells (Min et al, 2020). Previous studies have proposed that various circRNAs, such as circTP63 (Deng et al, 2021), circABCC4 addition, miRNA expression is also regulated by circRNAs, and circ-UBE2D2 could promote the malignant progression of BC through the adsorption of miR-1236 and miR-1287 (Hu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs are a sort of circular ncRNAs that widely exist in eukaryotes, and their structures are stable and highly conserved (H. D. Zhang, Jiang, et al, 2018). Researches have shown that circRNA is nearly connective with the pathogenesis of tumors and can effectively regulate tumor cells (Min et al, 2020). Previous studies have proposed that various circRNAs, such as circTP63 (Deng et al, 2021), circABCC4 addition, miRNA expression is also regulated by circRNAs, and circ-UBE2D2 could promote the malignant progression of BC through the adsorption of miR-1236 and miR-1287 (Hu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are a sort of circular ncRNAs that widely exist in eukaryotes, and their structures are stable and highly conserved (H. D. Zhang, Jiang, et al, 2018). Researches have shown that circRNA is nearly connective with the pathogenesis of tumors and can effectively regulate tumor cells (Min et al, 2020). Previous studies have proposed that various circRNAs, such as circTP63 (Deng et al, 2021), circABCC4 (J. Jiang & Cheng, 2020) and circRNA_0000518 (J. Jiang et al, 2020), promoted the development of breast cancer, while circNOL10 (Wang et al, 2021), circ_SETD2 (Shen et al, 2020) and circRNA_000554 (Mao et al, 2020) had inhibitory effects on the progression of BC.…”
Section: Discussionmentioning
confidence: 99%
“…As described in a previous study, BrdU staining assay was carried out to assess the proliferation of treated and/or transfected BC cells (Min et al., 2020). Specifically, BC cells to be tested were inoculated in a 6‐well plate with the required confluence of 70%, after which 10 μM BrdU solution (B8010, Solarbio, China) was added to culture the cells at 37°C for 4 h. The medium was subsequently discarded.…”
Section: Methodsmentioning
confidence: 99%
“…Circ_WWC3 upregulates the expression of multiple oncogenes in the RAS-signaling pathways by absorbing miR-26b-3p and miR-660-3p [ 55 ]. Several studies reported that other circRNAs also promoted cell migration and invasion; these circRNAs include circ_0011946 [ 56 ], circ_MMP11 [ 57 ], circ_0000291 [ 58 ], circ_MYO9B [ 59 ], and circ_RAD18 [ 60 ].…”
Section: The Dual Role Of Circrna As Mirna Sponges In Bcmentioning
confidence: 99%